Production of Additive‐Free Amorphous Nanoparticles with a SAW‐Based Microfluidic Spray‐Dryer. Issue 6 (8th May 2019) - Steinacher, Mathias; Du, Huachuan; Gilbert, Duncan; Amstad, Esther
Abstract: Spray‐drying is a widely employed, cost‐effective process to formulate solutions into solid particles of controlled sizes and compositions. In addition, this process can also offer control over the structure of spray‐dried particles: if the solvent is evaporated sufficiently quickly, crystallization of solutes can be kinetically suppressed, resulting in amorphous particles. To achieve the required fast drying of drops and to offer high flexibility in the solvent and solute choice, a surface acoustic wave (SAW)‐based spray‐dryer is introduced that produces drops with diameters of only a few micrometers. These small drops are dried in a dedicated drying unit at room temperature, thereby enabling the fabrication of additive‐free amorphous particles. This device offers an additional advantage: because the formation of drops is decoupled from their drying, chemical reactions can be initiated in drying drops using reactive gases without compromising the robustness of the device operation. This feature is demonstrated on aqueous drops encompassing Ca(OH)2 that are converted into amorphous CaCO3 particles using CO2 ‐enriched drying air. Because the solvent is evaporated at room temperature, this device offers new possibilities to process heat sensitive samples into powders with well‐defined compositions and unusual structures. Abstract : Surface acoustic waves (SAW) are employed to produce drops in the range of a few micrometers containing various solutes. Using room temperature gas, these drops are rapidly dried to suppress crystallization resulting in amorphous particles. The SAW‐based spray‐dryer is used to produce amorphous atenolol and CaCO3 particles.